DYNAmic Multi‐coIl TEchnique (DYNAMITE) shimming of the rat brain at 11.7 T. (17th May 2014) - Juchem, Christoph; Herman, Peter; Sanganahalli, Basavaraju G.; Brown, Peter B.; McIntyre, Scott; Nixon, Terence W.; Green, Dan; Hyder, Fahmeed; de Graaf, Robin A.
<x xml:space="preserve">Abstract</x> The in vivo rat model is a workhorse in neuroscience research, preclinical studies and drug development. A repertoire of MR tools has been developed for its investigation; however, high levels of B0 magnetic field homogeneity are required for meaningful results. The homogenization of magnetic fields in the rat brain, i.e. shimming, is a difficult task because of a multitude of complex, susceptibility‐induced field distortions. Conventional shimming with spherical harmonic (SH) functions is capable of compensating for shallow field distortions in limited areas, e.g. in the cortex, but performs poorly in difficult‐to‐shim subcortical structures or for the entire brain. Based on the recently introduced multi‐coil approach for magnetic field modeling, the DYNAmic Multi‐coIl TEchnique (DYNAMITE) is introduced for magnetic field shimming of the in vivo rat brain and its benefits for gradient‐echo echo‐planar imaging (EPI) are demonstrated. An integrated multi‐coil/radiofrequency (MC/RF) system comprising 48 individual localized DC coils for B0 shimming and a surface transceive RF coil has been developed that allows MR investigations of the anesthetized rat brain in vivo. DYNAMITE shimming with this MC/RF set‐up is shown to reduce the B0 standard deviation to a third of that achieved with current shim technology employing static first‐ through third‐order SH shapes. The EPI signal over the rat brain increased by 31%, and a 24% gain in usable EPI voxels could be realized. DYNAMITE shimming is expected to critically benefit a wide range of preclinical and neuroscientific MR research. Improved magnetic field homogeneity, together with the achievable large brain coverage of this method, will be crucial when signal pathways, cortical circuitry or the brain's default network are studied. Together with the efficiency gains of MC‐based shimming compared with SH approaches demonstrated recently, DYNAMITE shimming has the potential to replace conventional SH shim systems in small‐bore animal scanners. Copyright © 2014 John Wiley & Sons, Ltd.